PENGARUH DOSIS PUPUK KANDANG KOTORAN SAPI DAN NPK ANORGANIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI (Brassica juncea L.) - Ndiwa, Antonius S. S.; Oematan, Shirly S; Laiskodat, Imri M.H. (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2022)
This research was carried out in Oematnunu Village, West Kupang District, Kupang Regency and the study was carried out from February to April 2022. The aim of this study was to determine the effect of the dose of cow dung manure and inorganic NPK on the growth and yield of mustard plants. The purpose of this study was to determine the dose combination of cow dung manure and inorganic NPK fertilizer that could provide the best growth and yield of mustard plants. This study is a single factor experiment designed in a completely randomized design (CRD) with 5 treatments in the form of doses of rice straw mulch. Each treatment combination was repeated 6 (six) times so that a total of 30 experimental units were obtained.The results showed that 1). The combination of cow dung manure and inorganic NPK had a very significant effect on plant height, number of leaves, total fresh weight, and total net weight of mustard plants. 2). The combination treatment of manure dose of 5 tons/ha and NPK 300 kg/ha, combination dose of 10 tons/ha and NPK 200 kg/ha, and 400 kg/ha NPK fertilizer gave the best results on plant height, number of leaves, total fresh gross weight of mustard plant, and total net weight of mustard plant.